2020
DOI: 10.3389/fbioe.2020.595139
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Low-Magnitude High-Frequency Vibration on Bone Cells and Bone Regeneration

Abstract: Bone is a mechanosensitive tissue for which mechanical stimuli are crucial in maintaining its structure and function. Bone cells react to their biomechanical environment by activating molecular signaling pathways, which regulate their proliferation, differentiation, and matrix production. Bone implants influence the mechanical conditions in the adjacent bone tissue. Optimizing their mechanical properties can support bone regeneration. Furthermore, external biomechanical stimulation can be applied to improve im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 101 publications
0
25
0
3
Order By: Relevance
“…Cashion et al revealed that microvibration with a low frequency (1 Hz) induces chondrogenesis, whereas relatively high frequency (100 Hz) promotes osteogenesis ( Cashion et al, 2014 ). Thus, low-magnitude high-frequency vibration (LMHFV) (magnitude < 1 g, frequency 20–90 Hz) is generally used for osteogenesis ( Steppe et al, 2020 ). 50 Hz LMHFVs with different magnitudes (0.1, 0.3, 0.6, and 0.9 g) were used to stimulate PDLCs, and it was found that all groups promote osteogenic differentiation, but LMHFV with 0.3 g peaks the osteoinduction ( Zhang et al, 2015 ).…”
Section: Distinctive Biophysical Stimuli For Bone Tissue Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…Cashion et al revealed that microvibration with a low frequency (1 Hz) induces chondrogenesis, whereas relatively high frequency (100 Hz) promotes osteogenesis ( Cashion et al, 2014 ). Thus, low-magnitude high-frequency vibration (LMHFV) (magnitude < 1 g, frequency 20–90 Hz) is generally used for osteogenesis ( Steppe et al, 2020 ). 50 Hz LMHFVs with different magnitudes (0.1, 0.3, 0.6, and 0.9 g) were used to stimulate PDLCs, and it was found that all groups promote osteogenic differentiation, but LMHFV with 0.3 g peaks the osteoinduction ( Zhang et al, 2015 ).…”
Section: Distinctive Biophysical Stimuli For Bone Tissue Engineeringmentioning
confidence: 99%
“…Postoperative biophysical stimuli loading strategies are those methods that use noninvasive methods to generate biophysical stimuli to stimulate bone regeneration after surgery, including distraction osteogenesis (DO) ( Shah et al, 2021 ), LMHFV ( Steppe et al, 2020 ), LIPUS ( Hannemann et al, 2014 ), and PEMF ( Wang et al, 2019 ). These strategies have been clinically used to promote the healing of fractures; thus, their use can be extended to the treatment of critical bone defects.…”
Section: Applications Of Biophysical Stimuli For Bone Tissue Engineeringmentioning
confidence: 99%
“…It has been reported that androgen receptor disruption increases the osteogenic response to mechanical loading in male mice [176], while estrogen receptor beta regulates mechanical loading in primary osteoblasts [177]. More importantly, estrogen levels may also influence whether vibrations, loading and mechanical strain generate an anabolic effect on bone cells or not [124,125,127,178,179].…”
Section: Ossification Coactivatorsmentioning
confidence: 99%
“…However, if these stimuli become abnormal they can prevent restoration and rather aggravate the disease. Current topics of interest within experimental orthopaedic biomechanics include mechanical testing of normal and diseased musculoskeletal tissues [ 62 , 63 ], medical implant design and testing [ 64 ], tissue engineering [ 65 67 ] and translation of biomechanical into biochemical signals [ 68 71 ]. This research area will further optimize the biomechanical parameters of tissue-engineered implants and better understand cell- and drug-based therapeutic effects on mechanical behaviour at the tissue-level.…”
Section: Introductionmentioning
confidence: 99%
“…The role of extracellular matrix in instructing biochemical cascades in cells has become rather evident [ 74 , 75 ]. Also, materials that can closely mimic natural tissue properties and can navigate stem cell fates or exert immunomodulatory features are considered cutting edge [ 71 ]. The progress in developing such next generation biomaterials, that embrace the three-dimensional complexity of regenerating tissues as well as the interplay and optimal integration into the host tissue, can revolutionize biomaterial strategies in the near future.…”
Section: Introductionmentioning
confidence: 99%